2018
DOI: 10.1016/j.jid.2017.12.029
|View full text |Cite
|
Sign up to set email alerts
|

The Genetics of Chronic Itch: Gene Expression in the Skin of Patients with Atopic Dermatitis and Psoriasis with Severe Itch

Abstract: To identify itch-related mediators and receptors that are differentially expressed in pruritic skin, we used RNA sequencing to analyze the complete transcriptome in skin from paired itchy, lesional and nonitchy, nonlesional skin biopsies from 25 patients with atopic dermatitis and 25 patients with psoriasis and site-matched biopsies from 30 healthy controls. This analysis identified 18,000 differentially expressed genes common between itchy atopic and psoriatic skin compared with healthy skin. Of those, almost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
278
2
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(297 citation statements)
references
References 28 publications
9
278
2
8
Order By: Relevance
“…[17][18][19] The brain processes the itch signal, and motor activity (scratching) is induced. A few notable examples of pruritogen receptor-pruritogen pairs relevant to AD are as follows: (i) proteinase-associated receptor 2 (PAR2), which binds a pro-peptide released by mast cell proteases or house dust mite extract proteases 4,25 ; and (ii) several members of the Mas-related G protein-coupled receptor (Mrgprx) family, in particular Mrgprx2, which can be activated by the neuropeptide substance P. 16,[26][27][28] Many non-histaminergic pruritoceptors require the calcium ion channels TRPA1 and TRPV1 for itch signalling to the spinal cord. One system for functionally classifying groups of pruritoceptors is by sensitivity to histamine, a common pruritogen.…”
Section: Neural Pathways That Mediate Pruritus In Admentioning
confidence: 99%
“…[17][18][19] The brain processes the itch signal, and motor activity (scratching) is induced. A few notable examples of pruritogen receptor-pruritogen pairs relevant to AD are as follows: (i) proteinase-associated receptor 2 (PAR2), which binds a pro-peptide released by mast cell proteases or house dust mite extract proteases 4,25 ; and (ii) several members of the Mas-related G protein-coupled receptor (Mrgprx) family, in particular Mrgprx2, which can be activated by the neuropeptide substance P. 16,[26][27][28] Many non-histaminergic pruritoceptors require the calcium ion channels TRPA1 and TRPV1 for itch signalling to the spinal cord. One system for functionally classifying groups of pruritoceptors is by sensitivity to histamine, a common pruritogen.…”
Section: Neural Pathways That Mediate Pruritus In Admentioning
confidence: 99%
“…Interleukin 17 (IL‐17) has been thought to be able to modulate pruriception at the neuronal level of the dorsal root ganglia and the spinal cord . IL‐17A cytokine is overexpressed in itchy psoriatic skin; inhibition of IL‐17 via secukinumab or ixekizumab has improved itch in some studies, suggesting a potential role in itch induction . Similarly, some evidence suggests that IL‐31 has a potential role in inducing itch in psoriasis .…”
Section: Pathophysiology Of Itch In Psoriasismentioning
confidence: 99%
“…IL‐17A cytokine is overexpressed in itchy psoriatic skin; inhibition of IL‐17 via secukinumab or ixekizumab has improved itch in some studies, suggesting a potential role in itch induction . Similarly, some evidence suggests that IL‐31 has a potential role in inducing itch in psoriasis . However, other studies have found no clear correlation with itch intensity for either IL‐17 or IL‐31 .…”
Section: Pathophysiology Of Itch In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the signal from immuno‐reactive BNP is enhanced in skin from AD patients or from HDM‐treated mice (Meng et al, ; Figure ). Likewise, levels of BNP in the skin were increased in animal models of itch (Ewald et al, ; Liu et al, ; Meng et al, ), as well as in diseased skins with AD (Meng et al, ; Figure a) or psoriatic conditions (Meng et al, ; Nattkemper et al, ). We also observed that BNP level was increased in human prurigo nodularis skin (Figure a).…”
Section: Peripheral Role Of Bnp In Itchy Skinmentioning
confidence: 98%